GEO-ECONOMIC DEVELOPMENT OPPORTUNITIES FOR DANUBE MUNICIPALITIES IN THE CONTEXT OF REGIONAL INTEGRATION - Kamen Petrov (Journal of Bio-Based Marketing)
This paper presents an overview of the Danube municipalities on the Bulgarian coast, with a particular focus on their spatial and socio-economic characteristics as territorial units. The paper outlines the structural postulates that highlight the importance of the Danube coast for the regional development of the Danube region and the development of the Bulgarian geographical space. The paper goes on to present a characterization of the Danube region in a more general context as a part of the pan-European space, together with an outline of the development of socio-geographical processes and phenomena. In practice, the region presents many challenges for forming regional development policies and interest in the area in terms of tourism and investment. The paper presents relevant conclusions and recommendations for developing the Bulgarian municipalities along the Danube.